PID Controller Automatic Tuning Based Fuzzy Logic - عبد الحميد, رداح (Latakia University Journal -Engineering Sciences Series, 2021)
This paper shows the advantage of using fuzzy logic based Expert System in online-tuning PID parameters compared to traditional methods in order to obtain an output (control signal) with less stability time and better quality. It is known that the traditional methods of tuning the PID controller parameters are methods that depend on finding suitable values for the controller parameters during designing period, considering certain values of system parameters that can be changed during the operation. This can lead to a change in the response signal. Therefore, there is a real need for online tuning. This research studies the use of an Expert System used Fuzzy Logic Inference to automatically tuning (online) the PID controller based on a set of production rules obtained from experience derived from a careful study of the controller and the factors and variables affecting his performance. The research reached the result: The use of fuzzy control in determining the PID-controller parameters is effective and achieves various advantages, as it is a stable adaptive tuning of the controller with less response time and better output stability, comparable to those of the controller, whose parameters have been calculated using the traditional Ziegler-Nichols method.